Investigating Width Distribution of Slow and Fast CMEs in Solar Cycles 23 and 24 - Pant, V.; Majumdar, S.; Patel, R.; Chauhan, A.; Banerjee, D.; Gopalswamy, N. (Frontiers in Astronomy and Space Sciences, 2021)
Coronal Mass Ejections (CMEs) are highly dynamic events originating in the solar atmosphere, that show a wide range of kinematic properties and are the major drivers of the space weather. The angular width of the CMEs is a crucial parameter in the study of their kinematics. The fact that whether slow and fast CMEs (as based on their relative speed to the average solar wind speed) are associated with different processes at the location of their ejection is still debatable. Thus, in this study, we investigate their angular width to understand the differences between the slow and fast CMEs. We study the width distribution of slow and fast CMEs and find that they follow different power law distributions, with a power law indices ($α$) of -1.1 and -3.7 for fast and slow CMEs respectively. To reduce the projection effects, we further restrict our analysis to only limb events as derived from manual catalog and we find similar results. We then associate the slow and fast CMEs to their source regions, and classified the sources as Active Regions (ARs) and Prominence Eruptions (PEs). We find that slow and fast CMEs coming from ARs and PEs, also follow different power laws in their width distributions. This clearly hints towards a possibility that different mechanisms might be involved in the width expansion of slow and fast CMEs coming from different sources.These results are also crucial from the space weather perspective since the width of the CME is an important factor in that aspect.